Additional support needs policy in Scotland: challenging or reinforcing social inequality?. Issue 4 (3rd July 2016) - Riddell, Sheila; Weedon, Elisabet
ABSTRACT: This paper focuses on Scottish policy on additional support needs and its material outcomes. The central question addressed is the extent to which the Scottish additional support needs system undermines or reinforces existing social and economic inequalities. Administrative data highlight the inflation of the additional support needs category, particularly in relation to non-normative sub-categories such as social, emotional and behavioural difficulties which are strongly associated with social deprivation. Strategies in navigating the additional support needs system by families from different social class backgrounds are illustrated through short vignettes. The paper concludes with a discussion of the way in which sociological theory may help us to understand recent developments in Scottish additional support needs policy and practice. It is argued that the expansion of the umbrella category of additional support needs has been accompanied by an intensification of its association with social class, particularly in relation to categories which carry high levels of social stigma.